Impact of Thermal Properties on the Swelling Behavior of Polymer Composites Reinforced with Silica Xerogel - Fauziyah, Nur Aini; Fina Nidha Ulmu Fidha; Meiska Diah Kusumawardani; Putri Catur Kusumaningtyas; Primasari Cahya Wardhani; Dyah Suci Perwitasari (Chemistry Department, The University of Brawijaya, 2025)
This study investigates the swelling behavior and thermomechanical properties of polyethylene glycol (PEG) and silica xerogel composites using Dynamic Mechanical Analysis (DMA) and Differential Scanning Calorimetry (DSC). The composites were synthesized via a hydrothermal method and prepared by wet mixing PEG with silica xerogel. The analysis revealed that the interaction between PEG and silica xerogel significantly affects both the thermal and morphological properties of the composites. DSC data showed a shift in the glass transition temperature (Tg) and an earlier onset of thermal degradation in the PEG-Silica Xerogel 10 wt.% composite (P-SX10), indicating increased molecular mobility and reduced matrix stability. Notably, the swelling behavior was strongly influenced by temperature: as the temperature increased, the composites exhibited greater expansion and surface degradation, particularly in PEG-rich systems. This thermal sensitivity is attributed to the loosening of polymer–filler interactions and the partial debonding of matrix structures. The findings suggest that both composite composition and thermal exposure play critical roles in determining swelling characteristics and long-term structural integrity.